The Existence of Criminal Law Products in Dynamics Law Enforcement to Counter the Gambling Crime - Edi Santoso; Sri Kusriyah; Rakhmat Bowo Suharto (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to examine and analyze the form of existence of criminal law products that are applicable in law enforcement of gambling crimes. This research used a normative juridical method with research specifications in the form of descriptive analysis. Based on the discussion, it is concluded that the application of criminal sanctions against perpetrators of gambling crimes is related to the problem of applying the types of crimes and the length of punishment imposed on the perpetrators of the crime. In practice, the application of minimum criminal sanctions that have been imposed and the judge's decision (convict) still applies to the Criminal Code as the main system. Although Act No. 7 of 1974 concerning Gambling Control has been issued, it does not mean that the provisions in the Criminal Code will be set aside. This is because the laws and regulations do not make regulations or provisions that are specific or deviate from the Criminal Code. Although laws and regulations may make rules that deviate or are special from the main system (KUHP), it is still possible as long as the formulation policy includes guidelines for punishment. This provision is very necessary for the operationalization of the legislation. The Criminal Code (WvS) stipulates a fixed general minimum of one day and this is only contained in the explanation of the Article which contains it separately in accordance with the criminal threat.